Motif Dan Makna Komunikasi Mahasiswa Sebagai Wirausahawan Muda - Hantoro, Naditha Rizkya; Hasbiansyah, O.; Wiwitan, Tresna (Jayapangus Press, 2024)
In the era of globalization and technological advancement, the role of students as agents of change in society is increasingly recognized, especially through entrepreneurship and the importance of effective communication in the business world. This study aims to explore the motives and meaning of communication of students as young entrepreneurs. The focus of the research includes a discussion of the communication motives of students to become young entrepreneurs, as well as an understanding of the meaning of self, self-concept as a young entrepreneur, and the meaning of student communication as a young entrepreneur. The research method used is to use qualitative methods with a phenomenological approach with an interpretive paradigm. The results showed that the communication motives of students to become young entrepreneurs are based on two motives, namely because of motive (environmental motive, business potential motive, family economic conditions and limitations motive, hobby and passion motive) and in order to motive (motive to want to live independently and motive to get their own income). The self-meaning of students as young entrepreneurs is self-esteem and has a positive self-concept. This positive self-concept produces a multiplier effect. Students as young entrepreneurs interpret communication not only as a tool to convey information, but as a key element that forms the foundation of their business success, especially in establishing and developing a business.